An Analysis of Teachers’classroom Language at SMPN 4 Muara Bungo - Monica Sinta Bella; Yetty Zainil (Journal of English Language Teaching, 2020)
In the past two decades, there has been a significant increase in classroom interaction research on language use in the classroom. However, studies investigating teachers’ classroom language for junior high school are hard to find. The present research aims to figure out (1) teachers’ classroom language occurs in the teaching and learning process, and (2) teachers’ reflection on their classroom language. The study employed qualitative descriptive research with the three teachers of SMPN 4 Muara Bungo as the participants. Observation and Stimulated Recall Interview (SIR) were used to conduct the data, and the data were analyzed by using Salaberri’s handbook of classroom language (1995). The result of this study showed that teachers spoke six types out of 8 types of classroom language suggested by Sallaberi, namely simple instruction, dealing with the language of spontaneous situation, the language of social interaction, pair group work, question types, and dealing with error. However, the average of teacher’s English classroom language use showed a low percentage, which was only 45,4%. It proved that teachers in this study did not provide comprehensible input to their students. Through a stimulated recall interview, the teachers admitted that they are still not optimal in providing input to the students. It was because of two reasons: (1) students’ proficiency and (2) teachers’ proficiency themselves.